BIOAKTIVITAS ANTIOKSIDAN BIJI TUMBUHAN BINGKEK Entada phaseoloides merr) - Mubarrak, Jismi; Teruna, Hilwan Yuda; Ade, Filza Yulina; Khairina, Elfi (Universitas Pasir Pengaraian, 2015)
The use of plants as traditional medicine has long been known. One of them isBingkek (Entada phaseoloides merr). Seedl of this plant has been being used in folk medicine for stomach ache, hernias and restore the condition of women after childbirth, so as well as food. The study aimed to determine the antioxidant bioactivity of various fractions of seeds Bingkek and to identifity potential antioxidant compounds from this plant. The process started by macerating 500 g of seeds kernel by methanol. After 72 hours, the extract filtered and concentrated by rotary evaporator. Then, 80 g methanol exstract is fractioned by hexane, dicloromethane and athyl acetate. The result gained are 0.8 g hexane, dicloromethane 0.4 g, ethyl acetate 0.7 g and residual extract 23 g. the test result of each fraction antioxsidant bioactivity wit DPPH, showed 909,35 μg/mL hexane extract, 507,74 μg/mL dicloromethane, 712,61 μg/mL ethyl acetate and 77,60 μg/mL residual extract. The best value closest to vitamin C is the residual extract. Then, the phyrochemical profile showed that in residual extract contains phenolic compounds, triterpenoids, coumarin and saponins. It can be concluded that the residual extract has potential as good antioxidant. Further more it is necessary to carry out the study of of the potential compounds of the antioxidant.